Computed tomographic characteristics of craniomandibular osteopathy in 20 dogs - Pérez López, L. A.; Almansa Ruiz, J. C.; Steenkamp, G.; Holdsworth, A. (Frontiers in Veterinary Science, 2024)
Craniomandibular osteopathy (CMO) is a proliferative, self-limiting, non-neoplastic disease of growing dogs characterised by excessive new bone formation on the skull and mandible. The radiographic findings of CMO are well described; however, limited reports of the computed tomographic (CT) appearance are available. This paper aims to characterise the spectrum of CT findings that can occur with CMO. The study is retrospective, descriptive, multicenter, and includes 20 cases. Age at presentation ranged from 6 weeks to 12 months, with no sex predisposition. Scottish terriers were overrepresented (65%); other breeds included Cairn terrier, Jack Russell terrier, Staffordshire bull terrier, labrador retriever, golden retriever, akita and Slovakian rough-haired pointer (one of each breed). Terrier breeds represented 80% (16/20) of the patient cohort. Mandibular osteoproliferation was present in all patients (marked in 80%, bilateral in 95%), affecting the rostral mandible in 25%, body in 85%, and ramus in 80%. Tympanic bulla osteoproliferation was present in 60% (12/20) of patients (all marked, bilateral in 75%). Cranial osteoproliferation (frontal, parietal, temporal, occipital bones or maxilla, or combinations of them) was present in 90% (18/20) of patients (40% marked, 27% moderate, 33% mild). Nasopharyngeal narrowing was seen in all 12 patients with tympanic bulla osteoproliferation (67% marked, 27% moderate) and caused nearly complete occlusion in two of them. External ear canal stenosis was seen in 55% (11/20) of patients (63% marked, 37% moderate, all bilateral). Temporomandibular joint (TMJ) impingement was suspected in 83% (10/12) of patients with marked tympanic bulla osteoproliferation (75% bilateral). Osteolysis with a moth-eaten pattern was seen in the mandible of 10/20 dogs, the calvarium of 5/20 dogs, and the maxilla of 1/20 dogs (5%). Lymphadenomegaly (mandibular and medial retropharyngeal) was found in 15/20 patients (70% mild, 30% moderate). The most severe CT changes were seen in Scottish terriers. CT allows for detailed characterisation of the bony changes associated with CMO, including the effects occurring secondary to osteoproliferation surrounding the tympanic bullae such as TMJ impingement, external ear canal stenosis, and nasopharyngeal narrowing. Osteoproliferation affecting the cranium and the presence of osteolysis were seen more frequently in this study than previously reported in CMO.